Acute toxicity of zinc oxide nanoparticles to the rat olfactory system after intranasal instillation. Issue 10 (11th January 2013) - Gao, Lifeng; Yang, Sheng‐Tao; Li, Shaorui; Meng, Yuguang; Wang, Haifang; Lei, Hao
ABSTRACT: With the increased applications of zinc oxide (ZnO) nanoparticles (NPs), the toxicity of ZnO NPs arouses great concerns from the nano community and the general public. In this study, we report the toxicity of ZnO NPs (30 nm) to the rat olfactory system after intranasal instillation revealed by non‐invasive magnetic resonance imaging (MRI). MRI scans were performed on a 4.7‐T scanner at 1, 2, 3 and 7 days post‐exposure, and the histological changes of the rat olfactory epithelium were evaluated. The influences of chemical component and dispersant of the NPs were also investigated. In addition, an olfactory behavior test was performed. The MRI and histological results indicated that ZnO NPs induced significant damages to the olfactory epithelium, including disruption of the olfactory epithelial structures and inflammation. The destruction of mitochondria in epithelial cells was observed under transmission electron microscopy (TEM), suggesting that the possible toxicological mechanism might involve cellular energy metabolic dysfunction. Further, the lesion of the olfactory epithelium disturbed sniffing behaviors of the treated animals. The results suggest that MRI is potentially useful as a screening tool to assess the consequence of occupational exposure of ZnO NPs. Caution should therefore be taken during the use and disposal of ZnO NPs to prevent the unintended public health impacts. Copyright © 2012 John Wiley & Sons, Ltd. Abstract : ZnO nanoparticles are mass‐produced nanomaterials. In this study, we evaluated the acute toxic effects of 30 nm‐diameter ZnO nanoparticles after intranasal instillation by behavioral tests, magnetic resonance imaging and histology. It was shown ZnO nanoparticles instilled into the nasal cavity caused significant structural damages to rat olfactory epithelium (OE) and olfactory impairment. ZnO NP‐induced OE damages are characterized by edema, degeneration of epithelial cells and increased blood vessel permeability. The possible toxicological mechanism might involve cellular energy metabolic dysfunction.